Pengaruh Kualitas Produk dan Persepsi Harga terhadap Kepuasan Konsumen Pengguna Handphone Vivo - Nuravianti, Tika; Iskandar, Iskandar; Pratiwi, Rani Tania (STIE PENA, 2024)
The problem behind this research is the instability of sales of Vivo cell phones which are analyzed on consumer satisfaction of students from the Teacher Training and Education Faculty at Kuningan University. This is shown by data from 2019 according to data books or global cell phone usage data showing a figure of 7.8% more quarterly of VIVO cellphone users in 2019, in 2020 there was an increase showing a figure of 21.2% more quarterly of cellphone users, in 2021 the figure shows 7.4% per quarter of cellphone users, and in 2022 it will decline to 6.3% per quarter of cellphone users globally. This study aims to determine : (1) To describe the influence of product quality on consumer satisfaction with the VIVO cellphone brand for FKIP students at Kuningan University. (2) To describe the influence of price perception on consumer satisfaction with the VIVO cellphone brand for FKIP students at Kuningan University. (3) To describe the influence of product quality and price perception on consumer satisfaction of VIVO cellphone users among FKIP students at Kuningan University. The research method used in this research is a descriptive correlational research method. The subjects in this research were students from the Faculty of Teacher Training and Education, Kuningan University Class of 2021, 2022 and 2023 with a population of 1,046 students, and a sample of 139 samples using purposive sampling technique. Data collection techniques use documentation studies and questionnaires with a closed questionnaire model with a Likert scale. The data analysis technique in this research was carried out using multiple regression analysis. The research results show that: (1) Product quality has a positive and significant effect on consumer satisfaction with Vivo cellphone users among FKIP students at Kuningan University, (2) Price perception has a positive and significant effect on consumer satisfaction with Vivo cellphone users among FKIP students at Kuningan University. (3) Product Quality and Price Perception have a positive and significant effect on Consumer Satisfaction of Vivo Mobile Phone Users among FKIP students at Kuningan University.